Perceptions and Experiences of Postgraduate Students of Educational Management vis a vis Academic Jealousy - Tatık, Ramazan Şamil; Ayyıldız, Pınar (My University, 2023)
This study intends to reveal perceptions and experiences pertaining to postgraduate students of educational management related to the concept of academic jealousy. The study is a qualitative one designed with the understanding of Phenomenology. The participants consist of 10 students who had received and were receiving postgraduate education in the area of educational management. 1 of them is an academic, 6 are teachers, 1 is a manager in a non-governmental organization, and 2 are managers in public schools. Four semi-structured questions were asked during the focus group interview held via Google Meet. Content analysis was executed to analyze the data. Through the findings, it was obvious jealousy was experienced in academic/scientific publication processes and in the context of managerial duties/promotions in academic trajectories and through the competition between individuals. Academic jealousy seemingly harmed the involved individual, and individuals became isolated on account of academic competition. Addedly, academic jealousy had relevance to the individual's personality traits, rearing, the culture of the related organization, age, and workload. It was found the feeling of academic jealousy has a complex being and should be managed well. Consequently, academic jealousy carries the potential to harm individuals and higher education institutions. Academic leaders need to take individual psychological characteristics into account in their management style knowing when to intervene in team conflicts, create opportunities for learning, provide coaching and mentoring. Respect and concern for others, positive reinforcement, and open dialogue will be effective herbicide against envy weeds in academia. These key actions will help emerging researchers grow in a more supportive environment and minimize the devastating side effects of jealousy.
Keywords: Postgraduate education; educational management; Academic jealousy; postgraduate perceptions.